Energy-water optimization model incorporating rooftop water harvesting for lawn irrigation. (15th December 2015) - Wanjiru, Evan M.; Xia, Xiaohua
Highlights: Energy-water optimization with RWH for lawn irrigation is modeled. Potential daily energy cost saving of 14.3% is achieved. Potential daily water cost saving of 20.5% is achieved. Potential operational cost reduction of 15% is achieved. Pretoria method of pump's maintenance cost reduction is superior. Abstract: The management of energy and water is increasingly gaining attention among domestic end-users. In developing countries, potable water supply is unreliable leading to alternative strategies such as rooftop water harvesting (RWH), storage and pumping. Since urban garden irrigation is the highest outdoor water consumer, optimal scheduling is important to conserve energy and water over conventional lawn irrigation methods. A model to optimally control the lawn irrigation was developed with the simulation results showing 17.4% potential water savings when using water directly from municipal sources. With RWH of a 1-h event with 1-mm rainfall from a 120-m 2 roof, the model can potentially save 23.4% of water and 73.8% in energy costs per day. Such savings are important in reducing the demand for existing water and energy sources as well as greenhouse emissions. Further, this paper looks into two strategies to maximize the pump's life through minimizing the maintenance cost.